RESPECTING SHARIA OR OBSCURING INDENTITY? NON-MUSLIM WOMEN WEARING HIJAB IN ACEH FROM THE PERSPECTIVE OF THE MAJORITY - Muhammad Rio Fariza; Andre Noevi Rahmanto; Pawito Pawito (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
This study discusses how the majority Muslim community in Aceh responds to the use of the hijab by non-Muslim women in the context of the implementation of Islamic law. The implementation of the Islamic Sharia Qanun in Aceh requires Muslims to wear Islamic clothing. However, it does not apply to non-Muslims, although many non-Muslim women still choose to wear the hijab as a form of social adaptation. Using a qualitative approach and case study method, data were collected through in-depth interviews for one month with eight informants selected by purposive sampling, namely the majority Muslim community in Aceh and those around non-Muslim women who wear the hijab. Symbolic interaction theory analyzes the meaning created by the hijab symbol in social interaction. Gramsci's hegemony theory analyzes the dominance of the majority culture through social consensus without direct coercion. The results of the study show that the majority of Acehnese people accept the use of the hijab by non-Muslim women as a form of respect for local norms and culture. Most informants support this step, although there are concerns about the potential for blurring the identities between Muslims and non-Muslims. This study emphasizes the importance of religious tolerance and moderation to maintain social harmony in areas with religious plurality.